The well-grounded Java developer : vital techniques of Java 7 and polyglot programming - Evans, Benjamin J. (Manning, 2013)
This book takes a fresh and practical look at new Java 7 features, new JVM languages, and the array of supporting technologies you need for the next generation of Java-based software. You will find clear examples that are practical and that help you dig into dozens of valuable development techniques.